2022
DOI: 10.3390/curroncol29070402
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Follow-Up Program and Oncological Outcomes of Biliary Tract Cancer Patients after Curative-Intent Surgery: A Twenty-Year Experience in a Single Tertiary Medical Center

Abstract: Aim. The aim of this research was to assess the impact of an intensive follow-up program on BTC patients who had received surgery with curative intent at a tertiary referral hospital. Methods. BTC patients were followed-up every three months during the first two years after their first surgery and every six months from the third to the fifth post-operative year. Results. A total of 278 BTC patients who received R0/R1 surgery were included. A total of 17.7% of patients underwent a second surgery following disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…We discovered that 4 (11.4%) patients underwent surgery with the goal of curing them, that the projected median DFS of BTC patients was 5 months, and that 25% of these patients had a DFS of 6 months or more. In contrast, a retrospective analysis by Rizzo et al (Rizzo A. et al, 2022) found that between January 2000 and November 2020, the median DFS for R0 and R1 BTC patients who had surgery with the intention of curing the disease was 16.4 and 12.3 months, respectively. ( 663).…”
Section: Discussionmentioning
confidence: 94%
“…We discovered that 4 (11.4%) patients underwent surgery with the goal of curing them, that the projected median DFS of BTC patients was 5 months, and that 25% of these patients had a DFS of 6 months or more. In contrast, a retrospective analysis by Rizzo et al (Rizzo A. et al, 2022) found that between January 2000 and November 2020, the median DFS for R0 and R1 BTC patients who had surgery with the intention of curing the disease was 16.4 and 12.3 months, respectively. ( 663).…”
Section: Discussionmentioning
confidence: 94%
“…In fact, none of the 14 patients who received R0 repeat resection went on to experience disease recurrence. However, only 17% of patients were able to undergo surgery [ 5 ]. Other studies have also shown the benefit of repeat resection [ 6 - 7 ], and in conjunction with the evidence that adjuvant chemotherapy also improves outcomes, it becomes clear that appropriate surveillance guidelines are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to current guidelines, serial ctDNA monitoring has been shown to predict CRC recurrence up to 16.5 months before CT imaging, with a median lead time of 8.7 and 9.8 months [ 16 , 17 ]. This length of time may be the difference in whether or not patients are able to undergo repeat resection and if R0 resection may be achieved, providing a chance at increased RFS [ 5 - 7 ]. For those patients who are not selected for repeat surgery, ctDNA has also been used to guide adjuvant chemotherapy use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a minority of patients may qualify for surgical resection, the disease often exhibits a propensity for recurrence and metastasis even after radical surgery. Furthermore, the 5-year survival rate of patients remains dismally low, at <10%, accompanied by a staggering 1-year recurrence rate of ~60% (1)(2)(3). Additionally, CCA has exhibited resistance to systemic therapies, such as chemotherapy and targeted treatments.…”
Section: Introductionmentioning
confidence: 99%